Sustainability approaches to environmental justice and social power - Sze, Julie (New York New York University Press, 2018)
Sustainability and social justice remain elusive even though each is unattainable without the other. Across the industrialized West and Global South, unsustainable practices and social inequities exacerbate one another. How do social justice and sustainability connect? What does sustainability mean and, more importantly, how can we achieve it with justice? This volume tackles these questions, placing social justice and interdisciplinary approaches at the center of efforts for a more sustainable world. Contributors present empirical case studies that illustrate how sustainability can take place without contributing to social inequality. From indigenous land rights, climate conflict, militarization, and urban drought resilience, the book offers examples of ways in which sustainability and social justice strengthen one another> through an understanding of history, diverse cultural traditions, and complexity in relation to race, class, and gender, this volume demonstrates ways in which sustainability can help to shape better and more robust solutions to the world's most pressing problems.
Introduction / Julie Sze with Anne Rademacher, Tom Beamish, Liza Grandia, Jonathan London, Louis Warren, Beth Rose Middleton, and Mike Ziser. Part 1 Interdisciplinarity, place, and praxis : Situating sustainability from an ecological science perspective: ecosystem services, resilience, and environmental justice / M.L. Cadenasso and S.T.A. Pickett -- Situating new constellations of practice in the humanities: toward a just and sustainable future / Joni Adamson -- Situating sustainability against displacement: building campus-community collaboratives for environmental justice from the ground up / Giovanna Di Chiro and Laura Rigell -- Situating global policies within local realities: climate conflict from California to Latin America / Tracy Perkins and Aaron Soto-Karlin -- Situating urban drought resilience: theory, practice and sustainability science / Lawrence Baker. Part 2 Positionality, power, and situated sustainabilities : Indigenous lessons about sustainability are not just for "all humanity" / Kyle Whyte, Chris Caldwell, and Marie Schaefer -- Situating sustainability in the luxury city: toward a critical urban research agenda / Miriam Greenberg -- Man destroys nature?: gender, history, and the feminist praxis of situating sustainability / Traci Brynne Voyles -- I tano' i Chamorro/Chamorro land: situating sustainabilities through spatial justice and cultural perpetuation / Michael Lujan Bevacqua and Isa Ua Ceallaigh Bowman -- Equality in the air we breathe: police violence, pollution, and the politics of sustainability / Lindsey Dillon and Julie Sze. Afterword: from more than just sustainability to a more just resilience / David N. Pellow. Acknowledgments -- About the editor -- About the contributors -- Index.
Keywords: Sustainability; Social justice; Environmental justice